A Regioselective Domino Benzannulation Route to Indeno[1,2-a]fluorene-7,12-diones - Naik, Vijaykumar; Khan, Faiz Ahmed (Synthesis, 2024)
A base-promoted domino benzannulation reaction of 2,3-dibromoindenone with acyclic 1,3-dicarbonyls resulted in an efficient synthetic protocol for a series of novel polycyclic indeno[1,2-a]fluorenes. The reaction proceeds via the two sequential addition-elimination reactions of nucleophilic species generated from the 1,3-dicarbonyls under basic conditions, serendipitously leading to the benzannulation with two molecules of 2,3-dibromoindenone. The second addition-elimination occurs on the initially formed adduct of 1,3-dicarbonyl with 2,3-dibromoindenone, setting the stage for further intramolecular cyclization and aromatization. Interestingly, unsymmetrical 1,3-dicarbonyls furnished a single regioisomer. The origin of the regioselectivity and plausible mechanism is discussed.
Keywords: 2,3-dibromoindenone; indeno[1,2-a]fluorene; domino reaction; benzannulation; addition-elimination reaction